Evaluation of stray radiation to the operator for five hand-held dental X-ray devices - Smith, Richard (Dentomaxillofac Radiol, 2019)
OBJECTIVES: Evaluate stray radiation to the operator, as represented by a plane within the significant zone of occupancy (SZO), produced by five models of hand-held intraoral dental X-ray devices (HIDXDs). METHODS: The stray radiation for five models of HIDXDs was measured, using an anthropomorphic tissue-equivalent head phantom as a scattering object. An ionization chamber was used to measure the air kerma (μGy) at 63 positions in a 160 cm high by 60 cm wide plane that was 10 cm behind the X-ray device, identified as being within the SZO. RESULTS: Based on the measured air kerma from stray radiation of five different HIDXDs, the estimated annual air kerma at all measured spatial positions was calculated. When calculated using a median air kerma of 0.8 mGy at the distal end of the cone, as typically required for digital image receptors,(1) the ranges for estimated annual air kerma in the SZO across the devices were 0.14–0.77 mGy for the median, 0.41–1.01 mGy for the mean, and 1.32–2.55 mGy for the maximum. Similarly, when calculated using a median air kerma of 1.6 mGy as typically required for D-speed film,(2) the ranges for estimated annual air kerma across the devices were 0.28–1.54 mGy for the median, 0.83–2.03 mGy for the mean, and 2.64–5.10 mGy for the maximum. CONCLUSIONS: From measured air kerma values of stray radiation in the SZO, estimated annual exposures to the operator for HIDXDs are expected to be greater than from conventional wall-mounted or portable devices activated from a protected area (at a distance or behind shielding). HIDXDs should therefore only be used when patient accessibility makes their use necessary and the use of a portable device on a stand or a wall-mounted device is not reasonably feasible. This approach would keep occupational radiation exposures of dental workers as low as reasonably achievable.